Islamic Value Integrated Science E-Module for Junior High School Learning - Daffa Tantra Pratama; Suharsiwi Suharsiwi; Noor Azura Zakaria (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study addresses the persistent divide between scientific knowledge and Islamic values in junior high school learning by developing an Islamic value-integrated science e-module. Unlike prior studies that focus mainly on general digital media, this research emphasizes a structured, empirically validated module aligned with curriculum needs. The study employed a Research and Development (R&D) approach based on the Borg and Gall model, including needs analysis, design, development, expert validation, and usability testing. Data were collected from 100 teachers, four experts, and 60 students using questionnaires and validation instruments. The results indicate high feasibility scores from experts (88.13%–100%) and positive responses from teachers (89.65%) and students (81.30%). Qualitative findings indicate that the e-module improves students’ conceptual understanding of the circulatory system and fosters students’ awareness of Islamic values, particularly in recognizing the perfection of human creation. These findings suggest that integrating Islamic values into science e-modules supports both conceptual understanding and the development of religious character in a meaningful learning context.